DIRECT AND INDIRECT EFFECTS OF YOUTUBE CHILDREN SONGS ON THE L2ACQUISITION OF PRE-SCHOOL CHILDREN: A CASE STUDY - B. Babilonia, Angelilka; Claire R. Ibo, Revalyn; C Laxarno, Christina (SIGEH ELT : Journal of Literature and Linguistics, 2023)
This research aimed to look into direct and indirect effects of YouTube children songs on the L2 acquisition of preschool children. The researchers’ formulated three main questions in this study: (1) what is the effect of indirect exposure to YouTube children songs on the L2 acquisition of preschool child? (2) What is the effect of direct exposure to YouTube children songs on the L2 acquisition of preschool child? (3) Is there a significant difference between the children with direct and indirect exposure to YouTube children songs? To answer the research questions, the researchers utilized a qualitative research design. The researchers observed and recorded the session with the child for the data collection. Research ethics was properly observed in data gathering. Additionally, the researchers used a statistical tool to determine the significant difference in the participants L2 acquisition. Also, researchers used observational analysis to analyze the collected data from recorded video and test results. Furthermore, the findings showed that a child with direct exposure to YouTube songs shows more progress than a child with indirect exposure. Exposure to YouTube songs can help children learn because they can increase engagement, create a desired environment, improve concentration and memory, and keep children on task.